2020
DOI: 10.1038/s41467-019-13808-9
|View full text |Cite
|
Sign up to set email alerts
|

The RepID–CRL4 ubiquitin ligase complex regulates metaphase to anaphase transition via BUB3 degradation

Abstract: The spindle assembly checkpoint (SAC) prevents premature chromosome segregation by inactivating the anaphase promoting complex/cyclosome (APC/C) until all chromosomes are properly attached to mitotic spindles. Here we identify a role for Cullin-RING ubiquitin ligase complex 4 (CRL4), known for modulating DNA replication, as a crucial mitotic regulator that triggers the termination of the SAC and enables chromosome segregation. CRL4 is recruited to chromatin by the replication origin binding protein RepID/DCAF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 70 publications
(96 reference statements)
0
29
0
Order By: Relevance
“…DCAF14 (or PHIP, RepID) is one of 18 known CRL4 substrate receptors ( Jin et al, 2006 ). Human DCAF14 functions in mitogenesis ( Farhang-Fallah et al, 2002 ; Podcheko et al, 2007 ), replication origin initiation ( Zhang et al, 2016 ), and regulation of the spindle assembly checkpoint ( Jang et al, 2020 ). DCAF14 is also a prognostic biomarker for metastatic melanoma ( De Semir et al, 2012 ), and deleterious de novo mutations in DCAF14 are associated with developmental abnormalities ( Webster et al, 2016 ; Craddock et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…DCAF14 (or PHIP, RepID) is one of 18 known CRL4 substrate receptors ( Jin et al, 2006 ). Human DCAF14 functions in mitogenesis ( Farhang-Fallah et al, 2002 ; Podcheko et al, 2007 ), replication origin initiation ( Zhang et al, 2016 ), and regulation of the spindle assembly checkpoint ( Jang et al, 2020 ). DCAF14 is also a prognostic biomarker for metastatic melanoma ( De Semir et al, 2012 ), and deleterious de novo mutations in DCAF14 are associated with developmental abnormalities ( Webster et al, 2016 ; Craddock et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of other CRL4 substrates such as the histone methyltransferase SET8 or the CDK inhibitor p21, which is required for proper S-phase progression, prevention of spontaneous DNA damage and activation of the G2/M checkpoint, can also generate DSB (Jorgensen, Elvers et al 2007;Abbas, Sivaprasad et al 2008;Huen, Sy et al 2008;Kim, Starostina et al 2008;Liu, Lee et al 2009;Tardat, Brustel et al 2010). The BUB3-mediated delay in the metaphase-anaphase transition, followed by abnormal chromosomal segregation in RepID-deficient cells are also possibly associated with the occurrence of DNA damage foci (Janssen, van der Burg et al 2011, Jang, Nathans et al 2020a. RepID's functional domains mediate its interaction with chromatin and might underlie its role in regulating the DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has also illustrated that CRL4 Cul4/DDB1 E3 ubiquitin ligase regulates ovarian cancer drug resistance by targeting the anti-apoptotic protein BIRC3 [78] . Jang et al [79] further showed that deficiencies in RepID, CRL4, or RBBP7 delayed mitotic exit, increased genomic instability, and enhanced sensitivity of ovarian cacner cells to paclitaxel.…”
Section: Cullin-ring E3 Ubiquitin Ligasesmentioning
confidence: 99%